Pengaruh Inovasi Desain, Diferensiasi Produk Dan Ekuitas Merek Terhadap Keputusan Pembelian Laptop Merek Asus (Studi Kasus Mahasiswa Universitas Islam Malang) - Ramadhani, Angga; Wahono, Budi; Bastomi, Mohammad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the effect of design innovation, product differentiation and brand equity on purchasing decisions for Asus brand laptops. The independent variables in this study are design innovation, product differentiation and brand equity while the dependent variable is purchasing decisions. This study uses quantitative research. This study is a primary study using a questionnaire, the respondents are students of the Islamic University of Malang. This study uses a Likert scale as a method of collecting data. The respondents used were 80 students. It can be seen that the results of this study are that the design innovation variable has a positive and significant effect on purchasing decisions (0.000 <0.05), the product differentiation variable does not affect decisions of purchasing (0.783> 0.05) and brand equity variable has a significant effect on the purchasing decisions (0.049 <0.05). Keywords: Design Innovation, Product Differentiation, Brand Equity, Purchasing Decisions, Asus, Laptops.